Re-Visioning "Kamakura" Buddhism. Edited by Richard K. Payne. - Dankert, Michael J. (Buddhist Studies Review, 2003)
Re-Visioning "Kamakura" Buddhism. Edited by Richard K. Payne. (Kuroda Institute Studies in East Asian Buddhism No. 11), University of Hawai’i Press, Honolulu 1998. vii, 280 pp. Pb, 24.95. ISBN 0-8248-2078-9; (Hb. 50.00 - ISBN not known).